66.8k views
3 votes
Let x = wavelength and y = frequency. The equation that models the inverse relation is

Let x = wavelength and y = frequency. The equation that models the inverse relation-example-1
User WombaT
by
4.4k points

2 Answers

3 votes

Answer:

The Answer is D y= x/3x10squareroot8 m/s

Because its right on edg

User Philar
by
4.8k points
1 vote

Answer:

y = (3 × 10^8 m/s)/x

Explanation:

Speed of a wave is given by the product of wavelength and frequency.

Thus; speed = frequency × wavelength

If x = wavelength and y = frequency then speed will be;

speed = yx

Thus to get wavelength, y;

y = speed/x , but speed is 3 × 10^8 m/s

Thus;

y = (3 × 10^8 m/s)/x

User Jeremy McGee
by
4.8k points